PENGEMBALIAN IDENTITAS SENEN SEBAGAI SENTRA BUKU DENGAN METODE PLACEMAKING - Halim, Hartono; Surya, Rudy (Jurusan Arsitektur dan Perencanaan, 2025)
Senen is an area that is quite synonymous with booksellers since the 1970s. A famous bookstore, Gunung Agung, was also established in 1953 in Senen, Kwitang. Booksellers are also lined up along the roads in the Senen area, especially Kwitang. In 2008, the booksellers relocated, they moved to different places and some also rented a shophouse together in Kwitang. However, over the years, book sales and the number of visitors have decreased, especially during the pandemic. Senen's identity as an area synonymous with book sales also decreased due to advancing times so that the presence of printed books has been replaced by e-books. Even then, booksellers also complain about people’s low interest in reading.giving rise to a condition of